A nano-silver intercalated covalent organic framework polymer and its application
By inserting nanosilver layers into the covalent organic frame, PP-COF-Ag material was prepared, which solved the problem of easy agglomeration of silver nanoparticles and aggregation stacking of porphyrin polymers, significantly improved the photothermal and photodynamic properties of porphyrin photosensitizer, achieved efficient killing of drug-resistant bacteria, and had good biocompatibility.
Patent Information
- Application Number
- CN202411669153.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The prior art is difficult to effectively solve the problem of prone agglomeration of silver nanoparticles and the agglomeration and stacking of porphyrin polymers due to π-π action, resulting in poor photodynamic and photothermal effects of porphyrin photosensitizers loaded with silver nanoparticles.
Using 4,5-dihydroprene-4,5-dione and tetraaminophenylporphyrin as structural units, nanosilver intercalated covalent organic frame polymer (PP-COF-Ag) was prepared by intercalating nanosilver into a covalent organic frame to improve the utilization rate of silver nanoparticles and the photothermal and photodynamic properties of porphyrin photosensitizer.
Through the design of nano-silver interlayer, the layer spacing of the covalent organic frame is increased, the agglomeration of silver nanoparticles is prevented, the photothermal conversion efficiency and photodynamic performance are improved, and the effective killing of drug-resistant bacteria is achieved. The material has good biocompatibility and no toxic side effects.
Smart Images

Figure CN119176924B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedicine, and in particular to a nano silver intercalated covalent organic frame polymer and application thereof. Background Art
[0002] The prevalence of drug-resistant bacteria has brought unprecedented challenges to public health and economy worldwide. Non-antibiotic antimicrobial therapeutic strategies are targeted at unique infectious microenvironments (IMEs), such as hypoxia, pathological acidity, and overexpressed hydrogen peroxide, which have effective antibacterial effects on various strains. In the past few decades, many antibiotic-free antimicrobial modalities that cannot induce drug resistance have been developed as alternatives to antibiotics, such as thermal damage-based photothermal therapy (PTT) and reactive oxygen species (ROS)-based photodynamic therapy (PDT), enzyme therapy, and sonodynamic therapy (SDT). However, the practical application of these technologies has been challenged by various factors. For example, the limited oxygen concentration greatly hinders the efficiency of photodynamic therapy. PTT faces the challenge of therapeutic specificity, which inevitably leads to damage to normal tissues. In order to address all these issues simultaneously, in order to achieve satisfactory treatment results and reduce side effects, complex therapeutic strategies that can not only exert targeted therapeutic effects but also effectively reshape the pathological wound microenvironment are needed. However, traditional complex therapeutic drugs still face great challenges, including low active site density, poor selectivity, and specificity.
[0003] Porphyrin is a macromolecular heterocyclic compound. Metal organic framework polymers or covalent organic framework polymers prepared using porphyrin are widely used in antibacterial applications. Porphyrin has certain photosensitivity and can effectively release singlet oxygen under the action of ultraviolet or visible light. However, when porphyrin is used to prepare photosensitizers, porphyrin monomers aggregate through π-π action during the stacking process, and their photoactivity is quenched. The patent with application number CN202311648948.3 has a crown ether threaded covalent organic polyrotaxane framework material with an adaptive multi-nuclear zinc center and its preparation method and application. The organic framework material is reacted between aminoporphyrin and aldehyde compound 2,2-bipyridine-5,5-dicarboxaldehyde, and the crown ether is fixed on the organic framework material, and coordinated with zinc ions to load the polymer with zinc ions. Although zinc ions have antibacterial effects, they are far inferior to the antibacterial effects of silver ions, not to mention compared with silver nanoparticles. However, silver nanoparticles are easily agglomerated when loaded on organic framework materials, such as the patent of application number CN202311127047.X, a silver-based porous organic framework material and its preparation method and application, which uses the pyrrole reaction of crown ethers containing aldehyde groups and synthetic porphyrins to prepare organic framework materials, and then load silver nanoparticles. This polymer does not solve the problem of easy agglomeration of silver nanoparticles, and the utilization rate of silver needs to be improved. In addition, the problems of aggregation and stacking of porphyrin polymers through π-π effects undoubtedly affect the photodynamic and photothermal effects of porphyrin photosensitizers loaded with silver nanoparticles. Therefore, it is necessary to develop a method that does not agglomerate silver nanoparticles and solves the problem of aggregation and stacking of porphyrin polymers due to π-π effects, thereby greatly improving the photodynamic performance and photothermal performance of porphyrin photosensitizers loaded with silver nanoparticles. Summary of the invention
[0004] In view of the above-mentioned prior art, the purpose of the present invention is to provide a nanosilver intercalated covalent organic framework polymer and its application. The present invention uses 4,5-dihydropyrene-4,5-dione and tetraaminophenylporphyrin as structural units, and then obtains PP-COF-Ag by intercalating nanosilver into the covalent organic framework. The insertion of nanosilver increases the interlayer spacing of the original covalent organic framework, and can be combined with nanosilver, photothermal therapy and photodynamic therapy to achieve antibacterial effects, and has good biocompatibility and no toxic side effects.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] The first aspect of the present invention provides a nanosilver intercalated covalent organic frame polymer, wherein the nanosilver intercalated covalent organic frame polymer (PP-COF-Ag) is a porous material formed by stacking layers with 4,5-dihydropyrene-4,5-dione and tetraaminophenylporphyrin (TAPP) as structural units; silver nanoparticles are inserted into the layers of the nanosilver intercalated covalent organic frame polymer.
[0007] Preferably, 4,5-dihydropyrene-4,5-dione is prepared by the following method:
[0008] Pyrene and ruthenium trichloride hydrate (RuCl3xH2O) are dissolved in dichloromethane, and then acetonitrile and water are added, and then sodium periodate is added to react at room temperature to obtain 4,5-dihydropyrene-4,5-dione.
[0009] Preferably, the molar ratio of pyrene, sodium periodate and ruthenium trichloride hydrate is 1:4.2:0.1.
[0010] Preferably, the nanosilver intercalated covalent organic framework polymer is prepared by the following method:
[0011] (1) reacting 4,5-dihydropyrene-4,5-dione and tetraaminophenylporphyrin in an oil bath, and filtering, washing and drying in sequence after the reaction to obtain black powder PP-COF;
[0012] (2) PP-COF is added to methanol and ultrasonicated, and then the silver nitrate solution is added and ultrasonicated again, followed by a first stirring, the obtained precipitate is collected and dissolved in a mixed solvent, and a sodium borohydride methanol solution is added dropwise and a second stirring is performed to finally obtain a nanosilver intercalated covalent organic framework polymer.
[0013] Preferably, in step (1), the molar ratio of 4,5-dihydropyrene-4,5-dione to tetraaminophenylporphyrin is 2:1.
[0014] Preferably, in step (1), the temperature of the oil bath is 120° C.; and the reaction time is 72 h.
[0015] Preferably, in step (2), the ratio of the added amounts of PP-COF, methanol, silver nitrate solution, mixed solvent and sodium borohydride methanol solution is 75 mg: 45 mL: 6 mL: 30 mL: 1 mL.
[0016] Preferably, the concentration of the silver nitrate solution is 8.75 mg / mL; the mixed solvent is obtained by mixing methanol and water in a volume ratio of 3:2; and the concentration of the sodium borohydride methanol solution is 1 mol / L.
[0017] Preferably, in step (2), the first stirring time is 12 hours; and the second stirring time is 2 days.
[0018] The second aspect of the present invention provides the use of nanosilver intercalated covalent organic framework polymers in the preparation of antibacterial drugs.
[0019] Beneficial effects of the present invention:
[0020] (1) The nanosilver intercalated covalent organic framework material PP-COF-Ag prepared by the present invention can be combined with photothermal and photodynamic to synergistically inactivate bacteria. It has good photothermal conversion under 808 nm wavelength laser irradiation, and the induced electron transfer produces singlet oxygen, superoxide anion radicals, and hydroxyl radicals. It also has good simulated catalase (CAT) activity, which can not only selectively catalyze redundant hydrogen peroxide to produce oxygen, but also regulate the redox balance of the infectious microenvironment, which is beneficial to the growth of normal cells. O2 produced by catalyzing redundant hydrogen peroxide can effectively alleviate the hypoxia in the infectious microenvironment, but can also promote the generation of ROS and enhance the PDT effect with the O2-dependent photodynamic reaction cascade. The effect of nanosilver is attributed to its ability to enter the bacteria and combine with oxygen metabolic enzymes (-SH), causing the bacteria to suffocate and die. It has a strong killing ability against drug-resistant pathogens such as drug-resistant Escherichia coli and drug-resistant Staphylococcus aureus. The three strategies of nanosilver, photothermal therapy and photodynamic therapy are used to achieve combined broad-spectrum antibacterial.
[0021] (2) The preparation method of the present invention is simple, and the prepared PP-COF-Ag has good biocompatibility, a hemolysis rate of less than 1.5% on red blood cells, a slight effect on the vitality of HEK293 cells, and no toxic side effects on the human body, which will promote the development of a multifunctional antibacterial platform. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the infrared spectrum of PP-COF-Ag;
[0023] Figure 2 It is the performance characterization analysis diagram of PP-COF-Ag; a) is the solid-state NMR diagram of PP-COF-Ag; b) is the thermogravimetric analysis diagram of PP-COF-Ag; c) is the isothermal adsorption and desorption diagram of PP-COF-Ag at 77K; d) is the pore size distribution diagram of PP-COF-Ag;
[0024] Figure 3The SEM and TEM images of PP-COF-Ag, where (a) is the SEM of PP-COF at a scale of 5µm; (b) is the SEM of PP-COF at a scale of 2µm; (c) is the SEM of PP-COF-Ag at a scale of 1µm; (d) is the SEM of PP-COF-Ag at a scale of 2µm; (e) is the TEM of PP-COF at a scale of 1µm; (f) is the TEM of PP-COF at a scale of 500nm; (g) is the TEM of PP-COF at a scale of 50nm; (h) is the TEM of PP-COF at a scale of 10nm. TEM; (i) is the TEM of PP-COF-Ag at a scale of 1µm; (j) is the TEM of PP-COF-Ag at a scale of 500nm; (k) is the TEM of PP-COF-Ag at a scale of 50nm; (l) is the TEM of PP-COF-Ag at a scale of 10nm; (m) is the distribution of C element in PP-COF-Ag; (n) is the distribution of N element in PP-COF-Ag; (o) is the distribution of Ag element in PP-COF-Ag; (p) is the mapping diagram of PP-COF-Ag;
[0025] Figure 4 is the EDX image of PP-COF-Ag;
[0026] Figure 5 is the photothermal performance of PP-COF-Ag; where a) is at 1.3W / cm 2 The concentration-dependent photothermal effect of PP-COF-Ag under 808 nm laser irradiation; b) is the fitting curve of concentration and temperature for PP-COF-Ag (0~200μg / mL), laser (808 nm, 1.3 W / cm 2 ) is the irradiation time of 10 min; c) is the thermal imaging picture of the heating process of PP-COF-Ag 50~200μg / mL) within 10min laser irradiation; d) is the thermal imaging picture of the heating process of PP-COF-Ag 50~200μg / mL) within 10min laser irradiation; 2 Laser power-dependent photothermal effect of PP-COF-Ag under 808 nm laser irradiation; e) is the laser power-dependent photothermal effect of 808 nm laser at 1.3 W / cm 2 The temperature change curve of PP-COF-Ag (200 μg / mL) after four times of light cooling under the same conditions; f) is the negative natural logarithm of the cooling cycle and temperature during the heating and cooling process of PP-COF-Ag;
[0027] Figure 6 is the photodynamic performance of PP-COF-Ag, where a) DPBF under red light (808 nm, 1.3 W / cm 2) UV-visible spectrum under irradiation; b) PP-COF-Ag under red light (808 nm, 1.3 W / cm 2 ) UV-visible spectrum under irradiation; c) PP-COF-Ag under red light (808 nm, 1.3 W / cm 2 ) is the comparison of the decay rate of DPBF under irradiation; d) is the EPR spectra of PP-COF-Ag and TEMP in CH3CN under dark light and irradiation; e) UV-visible spectrum of MB under grating irradiation; f) UV-visible spectrum of MB and PP-COF-Ag under grating irradiation; g) Comparison of the decay rate of MB induced by PP-COF-Ag under 808 nm grating irradiation; h) is the EPR spectrum of PP-COF-Ag and DMPO in H2O under dark light and irradiation; i) Fluorescence spectrum of DHR123 under grating irradiation; j) Fluorescence spectrum of DHR123 and PP-COF-Ag under grating irradiation; k) Comparison of the decay rate of DHR123 induced by PP-COF-Ag under 808 nm grating irradiation; l) EPR spectrum of PP-COF-Ag and DMPO in CH3CN under dark light and irradiation;
[0028] Figure 7 is the antibacterial ability of PP-COF-Ag at different concentrations; a) is the culture diagram of Staphylococcus aureus and Escherichia coli after being treated with PP-COF-Ag at different concentrations; b) is the bacterial survival rate of Staphylococcus aureus and Escherichia coli determined by plate count method;
[0029] Figure 8 is the antibacterial performance of PP-COF-Ag; a) is the culture diagram of Staphylococcus aureus under different treatments; b) is the statistics of the survival rate of Staphylococcus aureus under different treatments; c) is the culture diagram of Escherichia coli under different treatments; d) is the statistics of the survival rate of Escherichia coli under different treatments;
[0030] Fig. 9 It is the transmission electron microscopy images of Staphylococcus aureus a) and Escherichia coli b) under 6 different treatments, the scale bar is 2.0 μm;
[0031] Fig.10 It is the biocompatibility experiment of PP-COF-Ag, where a) is the hemolysis rate of PP-COF-Ag with different concentrations; b) is the cell viability after incubation of HEK293 cells with PP-COF-Ag with different concentrations;
[0032] Fig.11 is a synthetic route diagram of an embodiment;
[0033] Fig.12is the photothermal effect and photodynamic performance of PP-COF; a) is the photothermal effect of PP-COF at different powers at 808 nm; b) is the concentration-dependent photothermal effect under 808 nm irradiation for 10 min; c) is the fitting curve of PP-COF concentration and temperature (0~200 µg / mL), laser (808 nm, 1.3 W / cm 2 ) irradiation time is 10 min; d) PP-COF + MB under red light (808 nm, 1.3 W / cm 2 ) UV-visible spectrum under irradiation; e) is the UV-visible spectrum of PP-COF + DHR 123 under red light (808 nm, 1.3 W / cm 2 ) is the fluorescence spectrum of PP-COF + DPBF under red light (808 nm, 1.3 W / cm 2 ) UV-visible spectrum under irradiation. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0035] As described in the background technology section, although silver nanoparticles have antibacterial effects, silver as a metal will reduce biocompatibility, and silver nanoparticles are prone to agglomeration. Porphyrin polymers are prone to aggregation and stacking through π-π interactions, which undoubtedly affects the antibacterial effect of porphyrin photosensitizers loaded with silver nanoparticles.
[0036] Based on this, the purpose of the present invention is to provide a nano-silver intercalated covalent organic framework polymer and its application. The present invention uses 4,5-dihydropyrene-4,5-dione and tetraaminophenylporphyrin as structural units, prepares a porous material PP-COF with a lamellar structure through a Schiff base reaction, and then reacts PP-COF with excess silver nitrate to load PP-COF with Ag. + , wash away the excess silver nitrate with water, then add sodium borohydride methanol solution, which not only reduces Ag + Silver nanoparticles are obtained, and nanosilver is intercalated into the PP-COF layer to obtain PP-COF-Ag, which has good biocompatibility, superior photothermal and photodynamic properties, and bacteria targeting effects that inorganic metal antibacterial agents do not have.
[0037] The nanosilver intercalated PP-COF in the present invention can open up the interlayer spacing of PP-COF, and at the same time prevent nanosilver from agglomerating, thereby improving the utilization rate of nanosilver, improving the utilization rate of porphyrin photosensitizer loaded with silver nanoparticles, and improving the biocompatibility, photothermal and photodynamic properties of the photosensitizer. In addition, conventional porphyrin photosensitizer treatment uses a 638 nm laser, because porphyrin aggregates through π-π action during the polymerization process, quenching its photoactivity, while the use of nanosilver expands the interlayer spacing, overcomes π-π stacking, and improves the performance of the photosensitizer; the PP-COF-Ag has good photothermal conversion under 808 nm wavelength laser irradiation, greatly reducing the energy required for illumination and reducing the possible damage of illumination to the human body. PP-COF-Ag can achieve local temperature rise through photothermal conversion to inactivate enzymes in bacteria and destroy their physiological structures, while combining the photodynamic effect to generate singlet oxygen, hydroxyl radicals and superoxide anions to oxidatively damage the bacterial structure to achieve better antibacterial effects. It also has good simulated catalase (CAT) activity, which can not only selectively catalyze redundant hydrogen peroxide to produce oxygen, but also regulate the redox balance of the infectious microenvironment, which is beneficial to the growth of normal cells. The O2 produced by catalyzing redundant hydrogen peroxide can effectively alleviate the hypoxia in the infectious microenvironment, but can also cascade with the O2-dependent photodynamic reaction to promote the production of ROS and enhance the PDT effect. The incorporation of nanosilver can also cause greater damage to structures such as bacterial cell membranes. At the same time, PP-COF-Ag has negligible hemolytic effect and minimal normal cell damage at the optimal antibacterial concentration, indicating that it has great potential in biomedicine.
[0038] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0039] Note: Unless otherwise specified, the water used in the present invention is distilled water, and the pH of PBS is neutral.
[0040] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0041] Example 1: Preparation of PP-COF-Ag
[0042] (1) Preparation of 4,5-dihydropyrene-4,5-dione
[0043] In a 500 mL round-bottom flask, pyrene (5 g, 24.72 mmol) and RuCl3xH2O (514.58 mg, 2.47 mmol) were dissolved in 60 mL of dichloromethane, and then 60 mL of acetonitrile and 70 mL of water were added to the solution. NaIO4 (22.20 g, 103.82 mmol) was added four times to obtain a dark brown suspension. The dark brown suspension was stirred at room temperature for 3 hours. The dark brown suspension was poured into water, and the organic phase was separated after filtering out the salt layer. The aqueous phase was extracted with dichloromethane to obtain an orange solution. Column chromatography was purified with dichloromethane / petroleum ether = 2:1 (v / v), and the pure product was bright orange crystals, namely 4,5-dihydropyrene-4,5-dione (4.65 g, yield: 81%).
[0044] (2) Preparation of tetraaminophenylporphyrin (TAPP)
[0045] 4-nitrobenzaldehyde (11 g, 0.073 mol) and acetic anhydride (12 mL, 0.127 mol) were added under nitrogen atmosphere, and 50 mL of propionic acid was added to dissolve it. Heat to reflux, slowly add pyrrole (5 mL, 0.172 mol), and after 4 hours, cool the resulting mixture, collect the precipitate by filtration, wash it with water and methanol in sequence, and dry it under vacuum. The resulting powder was dissolved in pyridine (25 mL) and refluxed for another 1.5 hours. Then cool, collect the precipitate after filtration, and wash it with acetone to obtain purple crystals. The purple crystals (2.5 g) were dissolved in 20 mL of concentrated hydrochloric acid (12 mol / L), and then tin chloride (7.0 g, 29 mmol) was added, and 65 mL of concentrated hydrochloric acid was added dropwise (drop speed 6.5 mL / min). The resulting mixture was stirred at room temperature for 2.5 h, then stirred at 80 ° C for 0.5 h, and then cooled to 0 ° C. A gray solid was obtained by vacuum filtration, and then the excess acid was removed with aqueous ammonia. Finally, the product was extracted and purified with chloroform to obtain a purple-black solid, namely TAPP (yield: 37%).
[0046] (3) Preparation of PP-COF
[0047] TAPP (33.7 mg, 0.05 mmol) and 4,5-dihydropyrene-4,5-dione (18.2 mg, 0.1 mmol) were added to 4 mL of trimethylbenzene and 0.2 mL of 3M acetic acid in a heat-resistant glass tube and ultrasonically treated for 10 minutes. After freeze-thaw degassing three times, the freeze-thaw bottle was sealed. The freeze-thaw bottle was then placed in an oil bath at 120°C for 72 hours. After the reaction was completed, a black precipitate was obtained by filtration. The precipitate was washed with anhydrous tetrahydrofuran, extracted with N,N-dimethylformamide using a Soxhlet extractor for 24 hours, and then dried at 80°C under vacuum for 12 hours to obtain PP-COF (yield 74%).
[0048] (4) Preparation of PP-COF-Ag
[0049] PP-COF (75.0 mg) was transferred to a 100 mL round-bottom flask containing 45 mL of methanol and sonicated continuously for 20 min. 6 mL of silver nitrate solution (concentration 8.75 mg / mL) was added, sonicated for 20 min, and then stirred for 12 h. The black solid was obtained by vacuum filtration and then washed twice with distilled water by centrifugation (9000 rpm, 5 min) to remove excess silver nitrate. The collected precipitate was added to a mixed solvent consisting of 18 mL of methanol and 12 mL of water. 1 mL of sodium borohydride methanol solution (1 mol / L) was added dropwise (drop speed 1 mL / min) and stirred for 2 days. After the reaction, the precipitate was collected by centrifugation (5000 rpm, 5 min). Wash with water and methanol three times in sequence, and centrifuge (9000 rpm, 5 min) to remove impurities such as free AgNPs. Finally, it was dried in a vacuum oven to obtain the target product PP-COF-Ag (yield: 63.7%). The synthetic route of this example is shown in Fig.11 .
[0050] Example 2: Characterization of PP-COF-Ag prepared in Example 1
[0051] (1) Figure 1 The infrared spectra of PP-COF-Ag prepared in Example 1 and the related monomers used in the synthesis prove the successful construction of PP-COF-Ag. The FT-infrared spectrum of PP-COF-Ag also integrates the benzene ring (1582 cm -1 ) and TAPP (1600, 1500, 1350 and 1177 cm -1 In addition to the characteristic peaks of porphyrin, the newly formed C=N bond (1610 cm -1 ) strong peak signal, C=O (1710 cm -1 ) is significantly weakened, indicating the consumption of free aldehyde after polymerization. The TAPP amino group (3340 cm -1 ) almost disappeared, indicating the consumption of free amino groups after polymerization. These results indicate the successful synthesis of the covalent organic framework.
[0052] (2) Figure 2 a) is the solid-state carbon spectrum of PP-COF-Ag, through solid 13 C -NMR further confirmed the skeleton structure of PP-COF-Ag. As shown in the figure, the resonance peak around 170 ppm is the characteristic peak of the imino bond (-C=N-) produced by the Schiff base reaction, and the aldehyde signal peak does not exist in the range of 190 ppm, proving that PP-COF-Ag is connected by the Schiff base reaction. The peak signals of benzene (100-125ppm) and porphyrin (125-142 ppm) can also be observed. These results further confirmed the successful establishment of PP-COF-Ag.
[0053] (3) Figure 2 b) is the thermogravimetric curve of PP-COF-Ag. Thermogravimetric analysis shows the thermal stability of PP-COF-Ag. The weight decrease within 100°C is due to the volatilization of water adsorbed in the material or residual organic solvent. There is no obvious change in weight at 100-300°C. The weight of PP-COF-Ag remains at 72.13% at 800°C, indicating that the prepared material has good thermal stability.
[0054] (4) Figure 2 c) is the low-temperature N2 absorption isotherm of PP-COF-Ag at 77 K. The porosity characteristics of the synthetic material PP-COF-Ag were determined by low-temperature nitrogen adsorption. Type III adsorption isotherm refers to a curve in which the adsorption amount increases slowly with the increase of relative pressure when the relative pressure is low, and the adsorption amount increases sharply in the area of high relative pressure. The lamellar material has a large plane surface. During the adsorption process, the adsorbate molecules are easily adsorbed on the lamellar surface in multiple layers. When the relative pressure is low, due to the weak adsorbate-adsorbent interaction, the adsorption is mainly monolayer or a small amount of multilayer adsorption, so the adsorption amount increases slowly; when the relative pressure is high, the adsorbate molecules such as nitrogen will undergo capillary condensation in the pores between the lamellar layers, causing the adsorption amount to increase rapidly. PP-COF-Ag presents a typical curve, which conforms to the characteristics of type III adsorption isotherm, and combined with TEM images, it shows that the material is a regular lamellar stacking structure. Figure 2 d) shows the pore size distribution curve drawn according to the nonlocal density functional theory (NLDFT) model, from which the pore distribution can be observed intuitively: the pores are concentrated in the range of 2–10 nm, but there are also pores of 10–100 nm.
[0055] (6) Figure 3 The following are the scanning electron microscope (SEM) and transmission electron microscope (TEM) images of PP-COF-Ag. It can be seen that PP-COF-Ag is a lamellar structure, which is composed of layers of polymers stacked one by one. High-resolution TEM shows that PP-COF-Ag has micropores, which is verified by light and shadow contrast. Figure 3 l) shows obvious lattice fringes, indicating that the polymer forms an ordered structure. Figure 3h) No obvious lattice fringes are seen; the distance of π-π interaction in PP-COF is about 0.3nm, while the diameter of the silver nanoparticles inserted in PP-COF-Ag is about 10nm. The insertion of nanosilver expands the interlayer spacing of PP-COF.
[0056] (7) Figure 3 (m)~ Figure 3 p) is the distribution of C, N, and Ag elements in PP-COF-Ag. From the Mapping, it can be seen that a large amount of C (67.96%), N (28.51%), and Ag (3.52%) are evenly distributed in PP-COF-Ag, which shows that the structural composition of the material has a certain uniformity. Figure 4 This is the EDX image of PP-COF-Ag. From the X-ray energy spectrum (EDX), we can find that C, N, and Ag elements are widely present.
[0057] (8) PP-COF-Ag was irradiated with 808 nm laser for 10 min to measure the photothermal effect of the material.
[0058] Figure 5 a) is at 1.3W / cm 2 The concentration-dependent photothermal effect of PP-COF-Ag under 808 nm laser irradiation shows that as the concentration of PP-COF-Ag increases, the temperature change caused by the heating of its suspension becomes larger and larger. Figure 5 b) is the relationship between the concentration of PP-COF-Ag and the temperature change, which means that the temperature change will continue to increase with the increase of concentration. Figure 5 c) is the thermal imaging picture of the heating process of PP-COF-Ag (0-200μg / mL) within 10 minutes. Figure 5 d) at 0.4, 0.7, 1.0 and 1.3 W / cm 2 Laser power-dependent photothermal effect of PP-COF-Ag under 808 nm laser irradiation. Figure 5 e) is 808nm laser at 1.3 W / cm 2 The temperature change curve of PP-COF-Ag (200μg / mL) was subjected to 4 cycles of light cooling under ON / OFF cycle irradiation. The temperature change of PP-COF-Ag was recorded. The results show that after 4 cycles (808nm, 1.3W / cm 2 ) showed good photothermal stability, and the highest temperature of the four cycles could reach about 68°C, and there was no obvious change in the temperature rise and cooling trend. The above results show that PP-COF-Ag has good photothermal effect and photothermal stability, making it a potential photothermal antibacterial agent.
[0059] Fig.12 a) ~ Fig.12 c) is the photothermal effect of PP-COF, where Fig.12 a) PP-COF at 0.4, 0.7, 1.0 and 1.3 W / cm 2 Laser power-dependent photothermal effect of PP-COF under 808 nm laser irradiation. Fig.12 b) is at 1.3W / cm 2 The concentration-dependent photothermal effect of PP-COF under 808 nm laser irradiation shows that as the concentration of PP-COF increases, the temperature change caused by the heating of its suspension becomes larger and larger. However, compared with PP-COF-Ag, the temperature change of PP-COF-Ag is significantly enhanced at the same concentration, indicating that the insertion of nanosilver increases the effectiveness of PP-COF heat transfer.
[0060] (9) Figure 5 f) is the PP-COF-Ag (200 μg / mL) aqueous dispersion under 808 nm laser irradiation (1.3 W / cm 2 ). When PP-COF-Ag (200µg / mL) was exposed to 808nm (1.3 W / cm 2 ) The calculated photothermal conversion efficiency is 85%. The calculation formula is obtained according to the photothermal conversion efficiency formula in the "A Photothermal-Fenton-like Reaction Artificial Nanozyme and Its Preparation Method and Application" disclosed in application number CN202310175497.X, where A 808 is the absorbance of PP-COF-Ag aqueous dispersion (200 µg / mL) at 808 nm, which is 1.1652.
[0061] (10) Photodynamic performance testing of PP-COF-Ag.
[0062] Figure 6 a) - Figure 6 c) The photodynamic properties of PP-COF-Ag were demonstrated. Using DPBF as a probe and 808nm laser as a light source, the photodynamic properties of PP-COF-Ag were detected by UV-visible spectroscopy. By controlling the laser irradiation time and monitoring the absorption intensity of DPBF (1 mg / mL, 30μL, DMSO as solvent) in the mixture (DPBF+PP-COF-Ag) at a wavelength of 418 nm, the ability of PP-COF-Ag to produce singlet oxygen was evaluated. The results showed that compared with the blank control (DPBF+light irradiation), the PP-COF-Ag+DPBF+light irradiation group (200μg / ml, 808nm laser 1.3 W / cm 2) A large amount of singlet oxygen can be produced in the first minute, and the peak value of DPBF drops significantly and rapidly, and the subsequent peak value decrease slows down. After 10 minutes of illumination, DPBF is consumed by 77%, which means that PP-COF-Ag produces a large amount of singlet oxygen under illumination.
[0063] (11) Figure 6 e) - Figure 6 g) shows the ability of PP-COF-Ag to generate hydroxyl radicals. MB (methylene blue) can react with hydroxyl radicals, causing its own color to disappear and its absorbance to decrease. Prepare 1 mg / mL MB probe (DMSO as solvent), take 30 μL, add it to 2 mL of water and 2 mL of PP-COF-Ag (200 μg / mL) water suspension, irradiate with 808 nm laser, and measure the absorption intensity at 660 nm wavelength every 0, 2, 4, 6, 8, and 10 minutes, so as to evaluate the ability of PP-COF-Ag to generate hydroxyl radicals. It can be seen that PP-COF-Ag has the effect of generating hydroxyl radicals after laser irradiation. The MB probe itself only decreased by less than 10%, while the absorbance decreased by 40% after mixing with PP-COF-Ag and 10 minutes of laser irradiation. This shows that PP-COF-Ag has a good ability to generate hydroxyl radicals.
[0064] (12) Figure 6 i)- Figure 6 k) The ability of PP-COF-Ag to generate superoxide anions is demonstrated. DHR123 (dihydrorhodamine 123) itself does not have fluorescence, but after contacting with superoxide anions, it is oxidized to become a fluorescent substance, so it can be used to detect superoxide anions. 1 mg / mL DHR123 probe (DMSO as solvent) was prepared, 3 μL was taken, and added to 2 ml PBS (pH=5.5) and 2 mL PBS (pH=5.5) suspension of PP-COF-Ag (200 μg / mL), respectively. It was irradiated with 808nm laser, and the fluorescence intensity at the emission wavelength of 500-600nm under 495nm wavelength excitation was measured every 0, 2, 4, 6, 8, and 10 minutes, thereby evaluating the ability of PP-COF-Ag to generate superoxide anions. It can be seen that the fluorescence intensity increased by 51% when only DHR123 was present, while it increased by 315% when PP-COF-Ag was added, indicating that PP-COF-Ag can generate a large amount of superoxide anions.
[0065] (13) Fig.12 d) - Fig.12f) The ability of PP-COF to generate hydroxyl radicals, superoxide anions, and singlet oxygen was evaluated. The concentrations of PP-COF and PP-COF-Ag were the same and the detection was carried out according to the method of (10) to (12). The results showed that under the same conditions, PP-COF-Ag had a stronger ability to generate hydroxyl radicals, superoxide anions, and singlet oxygen than PP-COF, indicating that the insertion of nanosilver can enhance the ability to generate reactive oxygen species.
[0066] (14) EPR detection of PP-COF-Ag. Figure 6 d) is the EPR spectra of PP-COF-Ag and TEMP in CH3CN under dark light and irradiation; Figure 6 h) is the EPR spectra of PP-COF-Ag and DMPO in H2O under dark light and irradiation; Figure 6 i) EPR spectra of PP-COF-Ag and DMPO in CH3CN under dark light and irradiation. Figure 6 d) It can be seen that in the dark, the EPR spectrum of PP-COF-Ag is a straight line, but after laser irradiation, a characteristic peak of hydroxyl radicals with a peak ratio of 1:2:2:1 appears, which proves the generation of TEMP-OH, indicating that the material can generate hydroxyl radicals after laser irradiation and be captured by the probe. Figure 6 h) shows that the EPR spectrum in the dark is also a straight line, while after 808 nm laser irradiation, a characteristic peak of superoxide anion with a peak ratio of 1:1:1:1 appears in the EPR spectrum, indicating that superoxide anion is generated after laser irradiation and is captured by the DMPO probe to form DMPO-O2• − The characteristic peaks appeared, proving that PP-COF-Ag can generate superoxide anions after laser irradiation. Figure 6 l) As can be seen, the EPR spectrum of PP-COF-Ag in a dark environment is a straight line, while after laser irradiation, a singlet oxygen characteristic peak with a peak ratio of 1:1:1 appears, indicating that singlet oxygen appears after laser irradiation, and the probe reacts with it to generate TEMP- 1 O2. The above data show that PP-COF-Ag does not produce reactive oxygen species in a dark environment, but can produce a variety of reactive oxygen species after laser irradiation, indicating that the material has both type II photodynamics and type I photodynamics.
[0067] Test Example 1: In vitro bacterial growth inhibition test
[0068] Take 5 mL of LB liquid medium and add it to the shaking tube. Use a bacterial picker to pick a colony from the evenly spread LB solid medium containing Staphylococcus aureus or Escherichia coli and place it in the above 5 mL of LB liquid medium. Place the shaking tube in a shaker and culture at 37°C for 8-12 hours until the final bacterial solution has an OD value of 0.1 at 600 nm (approximately equivalent to a bacterial concentration of 1×10 8 CPU / mL), and Staphylococcus aureus and Escherichia coli solutions were obtained respectively.
[0069] In order to verify the effect of PP-COF-Ag on bacterial activity, the PP-COF-Ag aqueous dispersion prepared in Example 1 with concentrations of 0 (blank group), 100, and 200 μg / mL was mixed with Staphylococcus aureus (1×10 8 CPU / mL) or Escherichia coli (1×10 8 CPU / mL) was mixed, and then pH 7 PBS was added to 1 mL. After 10 min of 808 nm (1.3 W / cm 2 ) laser irradiation treatment, and then cultured in a shaker at 37℃ for 8h. Different numbers of colonies were shown in the bacterial culture dish. Figure 7 a) is the culture diagram of Staphylococcus aureus and Escherichia coli after treatment with different concentrations of PP-COF-Ag; the antibacterial activity of PP-COF-Ag was then estimated by the plate count method. Figure 7 b) The bacterial survival rate of Staphylococcus aureus and Escherichia coli was determined by plate counting method; it was found that the number of Staphylococcus aureus and Escherichia coli colonies gradually decreased with the increase of PP-COF-Ag concentration. When the concentration of PP-COF-Ag reached 200µg / mL, the bactericidal effect of Staphylococcus aureus and Escherichia coli reached more than 90% after 10 minutes of irradiation.
[0070] To compare the antibacterial activities of photothermal and photodynamic effects, nanosilver effects, and the combination of the three, Staphylococcus aureus (1×10 8 CPU / mL) and Escherichia coli (1×10 8 CPU / mL). The specific groups were as follows: Group I: PBS, no light, Group II: PP-COF (200μg / mL, no light), Group III: PP-COF-Ag (200μg / mL, no light), Group IV: PBS+laser, Group V: PP-COF+laser (200μg / mL, 808nm laser, 1.3W / cm 2 , 10 min), Group VI: PP-COF-Ag + laser (200 μg / mL, 808 nm laser, 1.3 W / cm 2 , 10 minutes).
[0071] Depend on Figure 8 It can be seen that with the PBS group as the control group, a considerable number of colonies were observed in both Group I and Group IV. That is, regardless of whether laser irradiation was performed, there was no significant difference in the number of bacterial colonies in the PBS-treated group. Groups III and VI showed a certain bactericidal ability, and only showed a weak antibacterial ability similar to PBS under non-illumination conditions. PP-COF-Ag showed a significant antibacterial effect. The survival rates of Escherichia coli and Staphylococcus aureus after pure PP-COF treatment were 79.46% and 74.33%, respectively. After PP-COF-Ag treatment, the levels of Escherichia coli and Staphylococcus aureus were further reduced to 5.42% and 1.52%, respectively. This shows that PP-COF-Ag has a significant three-strategy combined broad-spectrum antibacterial performance.
[0072] Test Example 2: Transmission electron microscopy observation of bacterial morphology
[0073] To further understand the above antibacterial effects, TEM was used to study the changes in the morphological structure of Escherichia coli and Staphylococcus aureus ( Fig. 9 ), the group setting of this test example refers to the 6 groups in Test Example 1. The surface of Staphylococcus aureus in the PBS group (Group I) and PP-COF (Group II) is smooth and round, and the structure of Escherichia coli is complete and the flagella are clearly visible, indicating that PBS and PP-COF (without light) have no antibacterial effect on Staphylococcus aureus and Escherichia coli, while in the PP-COF-Ag group irradiated with laser, it can be clearly seen that Staphylococcus aureus and Escherichia coli died in large numbers. This shows that the antibacterial ability of the material is greatly improved under the triggering of laser irradiation, and the PP-COF-Ag+laser group (VI) has the best bactericidal effect.
[0074] Test Example 3: Hemolysis Test
[0075] Fresh blood was collected from female BALB / c mice weighing 20-25g (purchased from Jinan Pengyue Experimental Animal Breeding Co., Ltd.), and red blood cells were collected by centrifugation at 8000rpm for 10min, and washed three times with PBS until the supernatant was almost colorless. 300µL of red blood cells were mixed with 1000µL of PBS and mixed with PP-COF-Ag solution (concentration range of 50~250µg / mL, prepared by PBS) at a ratio of 1:9 (v / v), incubated in a shaker at 37℃ for 3h, and then centrifuged at 10000rpm for 20min. The hemolytic effect of PP-COF-Ag was detected by measuring the absorbance of each supernatant at 540nm by UV-visible spectroscopy. Distilled water was used as the positive control (+), and PBS was used as the negative control (-). Fig.10a) is the hemolysis rate of PP-COF-Ag at different concentrations on red blood cells. It was found that when the concentration of PP-COF-Ag increased from 50µg / mL to 250µg / mL, the hemolysis rate remained below 1.5%, which indicates that the material has good biocompatibility.
[0076] Test Example 4: Cytotoxicity Test
[0077] Cytotoxicity is also an important indicator for evaluating the biocompatibility of materials. Human embryonic kidney cells (HEK293 cells, purchased from TaiZe (Guangzhou) Biotechnology Co., Ltd.) were used for testing.
[0078] HEK293 cells were plated at 8 × 10 cells per well in a 96-well plate. 3 The cells were inoculated at a density of 100 μL per well, and 100 μL of cell suspension was added to each well. 100 μL of PBS was added to the surrounding duplicate wells for liquid sealing to prevent excessive evaporation. After 24 hours of incubation, different concentrations of PP-COF-Ag (50, 100, 150, 200, 300 μg / mL) and PBS (blank group) were added for treatment. After 24 hours, the supernatant was discarded, and the same volume of PBS (pH=7.4) containing 10 μL MTT (5 mg / mL) was added to each well. After 4 hours, the supernatant was aspirated, and 100 μL of DMSO was added to each well to dissolve the MTT-formamide crystals. After 5 minutes, the absorbance was measured at a wavelength of 490 nm in an ELISA reader. Fig.10 b) is the change of cell viability after incubation of HEK293 cells with different concentrations of PP-COF-Ag. It can be seen that with the increase of PP-COF-Ag concentration, the survival rate of HEK293 cells slowly decreased after 24 hours. It can be seen that the survival rate of HEK 293 cells after 24 hours of culture at 200 μg / mL is still higher than 80%. These results show that PP-COF-Ag has good biocompatibility at therapeutic concentrations, which once again shows that PP-COF-Ag has good biocompatibility.
[0079] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A nano-silver intercalated covalent organic framework polymer, characterized in that: The nano silver intercalation covalent organic frame polymer is a porous material formed by stacking sheets with 4,5-dihydropyrene-4,5-dione and tetraaminophenylporphyrin as structural units; silver nanoparticles are inserted into the sheets of the nano silver intercalation covalent organic frame polymer.
2. The nanosilver intercalated covalent organic framework polymer according to claim 1, characterized in that: 4,5-Dihydropyrene-4,5-dione was prepared by the following method: Pyrene and ruthenium trichloride hydrate are dissolved in dichloromethane, and then acetonitrile and water are added, and then sodium periodate is added to react at room temperature to obtain 4,5-dihydropyrene-4,5-dione.
3. The nanosilver intercalated covalent organic framework polymer according to claim 2, characterized in that: The molar ratio of pyrene, sodium periodate and ruthenium trichloride hydrate is 1:4.2:0.
1.
4. The nanosilver intercalated covalent organic framework polymer according to claim 1, characterized in that: The nano silver intercalated covalent organic framework polymer is prepared by the following method: (1) reacting 4,5-dihydropyrene-4,5-dione and tetraaminophenylporphyrin in an oil bath, and filtering, washing and drying in sequence after the reaction to obtain black powder PP-COF; (2) PP-COF is added to methanol and ultrasonicated, and then the silver nitrate solution is added and ultrasonicated again, followed by a first stirring, the obtained precipitate is collected and dissolved in a mixed solvent, and a sodium borohydride methanol solution is added dropwise and a second stirring is performed to finally obtain a nanosilver intercalated covalent organic framework polymer.
5. The nanosilver intercalated covalent organic framework polymer according to claim 4, characterized in that: In step (1), the molar ratio of 4,5-dihydropyrene-4,5-dione to tetraaminophenylporphyrin is 2:
1.
6. The nanosilver intercalated covalent organic framework polymer according to claim 4, characterized in that: In step (1), the temperature of the oil bath is 120° C.; and the reaction time is 72 h.
7. The nanosilver intercalated covalent organic framework polymer according to claim 4, characterized in that: In step (2), the ratio of the added amounts of PP-COF, methanol, silver nitrate solution, mixed solvent and sodium borohydride methanol solution is 75 mg: 45 mL: 6 mL: 30 mL: 1 mL.
8. The nanosilver intercalated covalent organic framework polymer according to claim 7, characterized in that: The concentration of the silver nitrate solution is 8.75 mg / mL; the mixed solvent is obtained by mixing methanol and water in a volume ratio of 3:2; and the concentration of the sodium borohydride methanol solution is 1 mol / L.
9. The nanosilver intercalated covalent organic framework polymer according to claim 4, characterized in that: In step (2), the first stirring time is 12 hours; the second stirring time is 2 days.
10. Use of the nanosilver intercalated covalent organic framework polymer according to any one of claims 1 to 9 in the preparation of antibacterial drugs.
Citation Information
Patent Citations
A photothermal-Fenton-like artificial nanozyme, its preparation method and application
CN115845086B
A silver-based porous organic framework material and its preparation method and application
CN117122703B
Crown ether threaded covalent organic polyrotaxane framework material with adaptive multi-core zinc center and preparation method and application thereof
CN117343257B
Novel porphyrin compound as well as preparation method and application thereof
CN107056792A
Porphyrin-based metal organic framework nano-carrier with sonodynamic combined starvation therapy anti-tumor function and preparation method of porphyrin-based metal organic framework nano-carrier
CN113117079A